In-plane behavior of tuff masonry panels strengthened with fibre-reinforced plastic cross layout - Marcari, G. (2010)
The paper is aimed at understanding the in-plane shear-compression behaviour of tuff masonry panels strengthened with FRP cross layout. Based on a previous experimental work carried out by some of the authors, a quantitative analysis of the contributions of FRP and bare masonry to reinforced panel shear capacity has been carried out. Force-displacement relationships of all the tested panels are provided, including the intermediate debonding strains. Finally, a critical comparison between the experimental masonry shear strength and the ones calculated according to analytical models suggested by the Italian code NTC 08 and the CNR-DT 200/2004 guideline is presented.